Characterization of the Constituents in Rat Biological Fluids After Oral Administration of Longshen Buyi Paste by High-Performance Liquid Chromatography/Quadrupole Time-of-Flight Mass Spectrometry - Zheng, Lu; Cong, Haijian; Yao, Zhongqing; Xue, Ming; Xiang, Ting; Wu, Bin (Asian Journal of Chemistry, 2014)
A high-performance liquid chromatography/quadrupole time-of-flight mass spectrometry method was established to detect as many constituents in rat biological fluids as possible after oral administration of Longshen Buyi Paste (LBP). A C18 column (3.5 μm particle size) was adopted to separate the samples and mass spectra were acquired in negative modes. First, the fingerprints of LBP were established, resulting in 20 components being detected within 70 min. Among these compounds, six compounds were tentatively identified by comparing the retention times and mass spectral data with those of reference standards and the reference literature. Other 14 components were tentatively assigned solely based on the MS data. in vivo, 4 components of LBP were observed in urine. This study developed a high-speed and sensitive method that was successfully utilized for screening the active ingredients of a Chinese medical formula and provided helpful chemical information for further pharmacology and active mechanism research on Chinese medicine.